Struktur dan Komposisi Mangrove Berdasarkan Tingkat Kerusakan di Segaraanakan Cilacap - Anwari, M. Sofwan; Sunarto; Dulbahri; Hadisusanto, Suwarno (Jurnal Wana Tropika, 2012)
The purpose of the study is to determine the structure, composition and regeneration ability mangrove vegetation. Structure and composition mangrove vegetation at Segaraanakan were studied by survey methods with stratified random sampling. Each individual of tree and sapling that account in the plot 100m2 was measured diameter of breast high and seedling was account total individual of each species in each plot 1 m2. The regeneration of each species was visualized by seeding number each station. The result of this study, 16 species and 9 genus have been identified. Domination mangrove vegetation different of each degradation level. The regeneration ability are Rhizophora apiculata was better than another. Keywords: Structure, composition, mangrove vegettaion, Segaraanakan